Cultural Expertise: If the Counsellor is to Become a Teacher, Toward What Should That Teaching Be Directed? - Ivey, Allen E. (Canadian Journal of Counselling and Psychotherapy, 2012)
The psychoeducational movement is presented as an important new challenge to the professional helper. Many, perhaps even most, helpers now find themselves engaged in the teaching of communication skills, decision-making, or any of a wide array of workshops. What is to be the relationship of these new duties to individual counselling? More important, toward what direction should these activities focus? This article presents the concept of "cultural expertise" as a goal construct for both counselling and psychoeducation.